The validity and reliability of a hydraulic resistance device for assessing resisted sprint time - Sašek, Matic; Cvjetičanin, Oskar; Šarabon, Nejc (Frontiers in Sports and Active Living, 2024)
The aim of this study was to assess the validity and reliability of a hydraulic resistance device (HRD) for monitoring sprint split times under different loads within and between sessions. Three 20-m sprints with low (15 N), medium-low (40 N), medium-high (50 N), and high (130 N) HRD resistance levels (loads) were performed on two separate occasions 14 days apart. Twenty-four student athletes (24.8 ± 3.8 years) participated in the first session and 13 (24.1 ± 3.2 years) of them in the second session. Resisted sprints split times over a distance of 0 to 20 m (t0-5, t0-10, t0-20, t5-10, t10-15, t15-20) were measured simultaneously with magnetic incremental encoder embedded in the HRD and a system of single-beam timing gates. The results showed acceptable to high within session (ICC3,1 = 0.91-0.99; CV = 0.92-3.38 %) and between session (ICC3,1 = 0.82-0.99; CV = 1.62-4.84 %) reliability of HRD for measuring all split times at all loads. The minimal detectable change between sessions ranged from 3.3 % at high load to 9.9 % at low load. The HRD systematically underestimated timing gates times at all loads (bias = 2.01-11.08 %), yet good to excellent consistency was observed between the HRD and timing gates, specifically for t0-10 and t0-20 (ICC3,k lower 95% CI = 0.84-0.99). Due to its high reliability and good validity in monitoring resisted sprint times, the HRD holds potential for practical and research applications.